Complications from the formation of preventive stomas in the surgical treatment of rectal cancer - I. I. Aliev; A. A. Smirnov; R. V. Pavlov; K. N. Komyak; D. A. Ivlev; N. A. Domanskiy; G. A. Sharygin; A. I. Nazmiev (Сибирский онкологический журнал)
Background. Anastomotic leakage is one of the most severe complications of colorectal cancer surgery. The formation of a preventive stoma can avoid the consequences of this complication. Given the increase in the rate of sphincter-preserving surgeries, the number of surgeries with the formation of preventive stoma has also increased significantly. There are several techniques and each of them has its advantages and disadvantages.The aim of the study was to compare the effectiveness of surgical treatment and techniques of preventive stoma formation.Material and Methods. The retrospective study included 353 patients with stage II–IV rectal cancer who underwent surgery with the formation of preventive stoma (110 with ileostomy formation, 243 with transversostomy) from 2016 to 2020. Both intraoperative parameters (operation time, blood loss, intraoperative complications) and postoperative parameters (postoperative bed-day, complications) were evaluated. Immediate complications within 30 days after surgery using the Clavien–Dindo complication scale and infectious complications mainly related to the stoma formation (prolapse, stoma retraction, presence of peristomal dermatitis, reoperation) were assessed.Conclusion. The choice in the formation of a preventive ileo- or transversostomy during rectal resection has no effect on the frequency of anastomosis failure; however, there is a tendency that patients with colostomy spend fewer bed days in a hospital. Stoma-related complications in the postoperative period are mild and can be treated conservatively in the vast majority of cases. In compliance with the standardized surgical procedures and the protocol of perioperative management of patients, the number of severe complications is minimal. It is necessary to evaluate the second step of management of patients with preventive stomas – their elimination.